Growth of the wild potato Solanum commersonii (Solanaceae) among grass tussocks under different defoliation intensities = Crecimiento de la papa silvestre Solanum commersonii (Solanaceae) entre matas de gramíneas bajo diferentes intensidades de defoliación - Vignolio, Osvaldo (2018)
Solanum commersonii is a wild potato, valuable as a socioeconomic resource for a breeding program of feeding crops. In grasslands, this species grows associated to Paspalum quadrifarium, a forage grass managed under grazing conditions. We are interested in knowing in S. commersonii plants a) if they are benefied growing together with P. quadrifarium plants, b) the effects of defoliation on growth, reproduction and survival, and c) if the vegetative and reproductive atributes of the plants differ with sampling site. Potato seeds were collected in two sampling sites of the Paititi Natural Reserve (Buenos Aires, Argentina), the lowest and highest. One potato plant per pot was cultivated. Under greenhouse conditions, it was analyzed the effect of two defoliation intensities, low and high, 50 and 75% plant height reduction compared to pre-defoliation, respectively. Under field conditions, S. commersonii plants were placed among P. quadrifarium tussocks. Control plants were placed outside of the tussocks, on short grass. Defoliation did not cause plant mortality and these regrew through sprouting from stolons. Stems, leaves and total biomass were significantly affected by defoliation intensity. Defoliation intensity also affected green leaves area and height per plant. Plants of the highest site developed more stems and tubers number and green leaves area than from the lowest site. Paspalum quadrifarium architecture generated thermal conditions that were more benign for S. commesonii plant growth. During winter, night temperature was lower (freezing) in control conditions than among tussocks. Shoot dead biomass of the control potato plants was 67% and 13% in the plants growing among P. quadrifarium tussocks. One hundred percent of control plants developed tubers, meanwhile those growing among tussocks only developed the 55%. Berries were only produced in control plants, 1.56 and 0.56 g/plant, in the highest and lowest sites, respectively.